Cu2+ Inhibits the Peroxidase and Antibacterial Activity of Homodimer Hemoglobin From Blood Clam Tegillarca granosa by Destroying Its Heme Pocket Structure - Wang, Sufang; Yu, Xiaopei; Zhang, Shunqin; Jin, Hongyu; Chen, Zhongfa; Lin, Zhihua; Bao, Yongbo (Frontiers in Marine Science, 2021)
Beyond its role as an oxygen transport protein, the homodimer hemoglobin of blood clam Tegillarca granosa (Tg-HbI) has been found to possess antibacterial activity. However，the mechanism of antibacterial activity of Tg-HbI remain to be investigated. In this study, we investigated the effects of Cu2+ on the structure, peroxidase activity, and antibacterial ability of Tg-HbI. Tg-HbI was significantly inactivated by Cu2+ in a noncompetitive inhibition manner, following first-order reaction kinetics. The Spectroscopy results showed that Cu2+ changed the iron porphyrin ring and the coordination of heme with proximal histidine of Tg-HbI, and increased the hydrophobicity of heme pocket. We found that proline could stabilize the heme pocket of Tg-HbI, hence, protect peroxidase activity and antimicrobial activity of Tg-HbI against damage by Cu2+. Our results suggest that Cu2+ inhibits the peroxidase and antibacterial activity of Tg-HbI by destroying its heme pocket structure and Tg-HbI probably plays an antibacterial role through its peroxidase activity. This result could provide insights into the antibacterial mechanism of Tg-HbI.